(untitled) (SAARC Journal of Agriculture, 2015)
The productivity of arid legumes in arid and semi-arid tracks remains virtually stagnant over decades because of their susceptibility to root diseases. The information on interaction of beneficial nitrogen fixing rhizobia with particular reference to arid legumes of the region is limited. Systematic studies on predominant species Sinorhizobium saheli in management of root pathogens in arid legumes were undertaken. In-vitro interactions of root pathogens and S. saheli isolated from arid legumes significantly suppressed the growth of all fungal pathogens in presence of S. saheli. In addition the growth of Rhizobium was stimulated in presence of different root pathogens. A field experiment on integrated disease managementexhibited that the maximum root nodulation with the maximum seed yield of 1325 kg/ha was observed from treatment where seeds were treated with S. saheli. Whereas, the minimum root nodulation was recorded in treatment, where a mixture of isolated fungal root pathogens were co-inoculated with S. Saheli was recorded from cowpea. The minimum seed yield was recorded from treatment wherein the mixture of isolated root pathogens of arid legumes was co-inoculated with S. Saheli due to increased disease pressure. The results of in-vitro and in-vivo efficacy of S. saheli strains suggest that their co-inoculation with PGPRs can not only reduce the use of chemical fertilizers but also can significantly enhance yields by increasing plant growth and suppressing soil borne plant pathogenic fungi. SAARC J. Agri., 13(1): 63-74 (2015)